2022
DOI: 10.3390/molecules27020336
|View full text |Cite
|
Sign up to set email alerts
|

Potential Associations among Bioactive Molecules, Antioxidant Activity and Resveratrol Production in Vitis vinifera Fruits of North America

Abstract: Grapes (Vitis vinifera L.) are rich in bioactive molecules contributing to health benefits. Consumption of grapes is linked to reduced incidence of cardiovascular diseases. Studies on table grape cultivars are limited although much attention in research was focused on the wine industry. Bioactive effects of grapes as anti-inflammatory, anticarcinogenic, cardioprotective, vasorelaxant, phytoestrogenic and neuroprotective have also been reported. For example, resveratrol is a natural food ingredient present in g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 31 publications
1
14
0
1
Order By: Relevance
“…9 Grapes (Vitis vinifera L.) are one of the natural ingredients that contain anthocyanins, especially in the fruit's skin. 10,11 In addition, grape skin contains total phenols (168.55 mg/100 g), flavonoids (61.10 mg/100 g) and IC 50 of 1,065 ppm. 11 In another study, it was also found that grape skins and grape seeds, which are wastes in the wine-making process, can reduce hyperlipidemia, 12 which is caused by antioxidants present in grape skins and grape seeds.…”
Section: Discussionmentioning
confidence: 99%
“…9 Grapes (Vitis vinifera L.) are one of the natural ingredients that contain anthocyanins, especially in the fruit's skin. 10,11 In addition, grape skin contains total phenols (168.55 mg/100 g), flavonoids (61.10 mg/100 g) and IC 50 of 1,065 ppm. 11 In another study, it was also found that grape skins and grape seeds, which are wastes in the wine-making process, can reduce hyperlipidemia, 12 which is caused by antioxidants present in grape skins and grape seeds.…”
Section: Discussionmentioning
confidence: 99%
“…A detailed overview of bioactive compounds, extraction methods (Table 2), and health benefits of grapes is given in Table 1. Wijekoon et al (2022) studied the antioxidant effects, fatty acid composition, and phenolic content of four different types of grapes. The phenolic compounds, such as caffeic acid, quercetin, and resveratrol, were abundant in Red Globe type of grapes and unsaturated fatty acids.…”
Section: Grapesmentioning
confidence: 99%
“…Wijekoon et al (2022) extracted phenolic compounds from grape berries based on(Romero-Pérez et al, 2001). Freeze-dried grapes kept well at −80 • C. One gram of each kind was weighed and placed into 50 mL centrifuge tubes, and then the whole mixture was pulverized in a mortar and pestle.…”
mentioning
confidence: 99%
“…Research, Society and Development, v. 11, n. 9, e49211932221, 2022 (CC BY 4.0) Fan et al, 2022Leal et al, 2017Wijekoon et al, 2022Cardile et al, 2005Jiang et al, 2020Piotrowska et al, 2012Yamamoto et al, 2020Potter et al, 2002Matsui et al, 2010FerrignI et al, 1984Lee et al, 2022Know et al, 2022Algandaby e Al-Sawahli, 2021Yang et al, 2020Kroplewska et al, 2019Kido et al, 2020Shi et al, 2020Sato et al, 2022Baseggio et al, 2022Sáez et al, 2018Arai et al, 2016Banik et al, 2020Kawakami et al, 2014Kershaw e Kim, 2017Kukreja et al, 2014Osamudiamen et al, 2020Park et al, 2021Setoguchi et al, 2014King et al, 1956Silva et al, 2021Misuzaki et al, 2017Pan et al, 2020Zomer et al, 2022Viñas et al, 2011Vinãs et al, 2009Zachová et al, 2018Avendaño-Godoy et al, 2022Lai et al, 2014Rimando et al, 2004 Xie e Bolling, 2014 Ersan et al, 2020Ku et al, 2005Santos et al, 2017Boue et al, 2013 Fonte: Autores.…”
Section: Metodologiamentioning
confidence: 99%
“…Dentre as 72 espécies, o amendoim (Arachis hypogacea), o eucalipto (Eucalyptus wandoo) e a uva (Vitis vinífera e Vitis labrusca) são as espécies nas quais o resveratrol é encontrado em maiores quantidades. Além disso, o resveratrol também está presente em outras fontes naturais como mirtilo, uvas de outras espécies, cacau e morango, porém em quantidades menores (Fan et al, 2022;Leal et al, 2017;Lelákova et al, 2019;Wijekoon et al, 2022).…”
Section: Estilbenosunclassified